2014
DOI: 10.4314/tjpr.v13i2.20
|View full text |Cite
|
Sign up to set email alerts
|

Discriminatory Attitudes of Pharmacy Students and Pharmacists against People Living with HIV/AIDS

Abstract: Purpose: To evaluate the level and predictors of discriminatory attitudes of pharmacy students and pharmacists towards people living with HIV/AIDS (PLWHA). Methods:A cross-sectional survey of pharmacy students and pharmacists (n = 523)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…8 However, inaccurate HIV transmission knowledge can increase negative perceptions and attitudes resulting in stigmatization against those who are infected. 9,10 Such stigmatization can negatively impact access to social support, which is a reported buffer against stigma, because people are afraid of disclosing their HIV status to others. 11,12 Ultimately, HIV stigma can negatively impact success of HIV prevention strategies such as: HIV testing, HIV disclosure, medication adherence, and consistent condom use because of fear of rejection, ostracizing, domestic violence, and lack of privacy and confidentiality.…”
Section: Introductionmentioning
confidence: 99%
“…8 However, inaccurate HIV transmission knowledge can increase negative perceptions and attitudes resulting in stigmatization against those who are infected. 9,10 Such stigmatization can negatively impact access to social support, which is a reported buffer against stigma, because people are afraid of disclosing their HIV status to others. 11,12 Ultimately, HIV stigma can negatively impact success of HIV prevention strategies such as: HIV testing, HIV disclosure, medication adherence, and consistent condom use because of fear of rejection, ostracizing, domestic violence, and lack of privacy and confidentiality.…”
Section: Introductionmentioning
confidence: 99%
“…We found that two-thirds of the respondents in Kelantan had negative attitudes towards PLWHA, similar to the findings in the study by Khan and Baig (2013), which reported that a majority of the hospital pharmacists in Kedah also had negative attitudes towards PLWHA. Discriminatory attitudes of pharmacist against PLWHA were also being reported in Nigeria (Ubaka, Adibe, & Ukwe, 2014). Nevertheless, pharmacists in Iraq showed positive attitude towards PLWHA in providing care and treatment (Allela, Shareef, & Ismael, 2017).…”
Section: Discussionmentioning
confidence: 95%
“…10 A study shows discriminatory attitude of pharmacy students and Pharmacists against HIV patients. 11 A study shows that pharmacy students have good knowledge; however certain misconceptions and negative beliefs remain. 12 In this study, focused to assess the knowledge and attitude of pharmacy students from Mumbai University towards HIV.…”
Section: Discussionmentioning
confidence: 99%